2013
DOI: 10.1080/00288330.2013.808236
|View full text |Cite
|
Sign up to set email alerts
|

Fish physiology and ecology: the contribution of the Leigh Laboratory to the collision of paradigms

Abstract: The often pragmatic division of studies of function (physiology), and the regulation of distribution and abundance of organisms (ecology), as laboratory and field studies respectively, can create an unhelpful intellectual division that runs the risk of ignoring the interaction of physiology, behaviour and environment that regulates the lives of animals in the wild. This review examines the historical and current contribution of ecophysiological research conducted from the University of Auckland's Leigh Laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
1
1
0
Order By: Relevance
“…Continuous darkness (0 L: 24D) was found to be adverse effect on the welfare of T. fasciata which had resulted into the mortality of two individuals of fish. Chronic stress may be responsible for welfare impairment while acute stress might be a reason for the mortality of two fish in the present study as reported by Pickering (1998) and Damsgard et al (2006) in their research works. The unfavourable photoperiods could have affected the immune systems of the species resulted in the observed deviations in the normal welfare behaviour of the giant gourami as reported by Mustapha et al (2014).…”
Section: Discussionsupporting
confidence: 76%
“…Continuous darkness (0 L: 24D) was found to be adverse effect on the welfare of T. fasciata which had resulted into the mortality of two individuals of fish. Chronic stress may be responsible for welfare impairment while acute stress might be a reason for the mortality of two fish in the present study as reported by Pickering (1998) and Damsgard et al (2006) in their research works. The unfavourable photoperiods could have affected the immune systems of the species resulted in the observed deviations in the normal welfare behaviour of the giant gourami as reported by Mustapha et al (2014).…”
Section: Discussionsupporting
confidence: 76%
“…Some of the lessons learned here have been forgotten by some subsequent workers, for example the importance of stratifying by depth when examining fishÁ habitat relationships. Other techniques were developed to sample plankton (Kingsford 2013) and to conduct physiological measurements on fish (Montgomery & Radford 2013;Pankhurst & Herbert 2013). The Cape Rodney to Okakari Point Marine Reserve is one of the world's first 'no-take' marine reserves.…”
mentioning
confidence: 99%